This formula used to convert transmitter Linear ma to Square root ma conversion.Calculating the equivalent Square root ma for any given Linear ma.

## Formula for Linear ma to Square root ma conversion

**Formula:**

### Square root mA = { √ [(X-4)/16] } .16 + 4

Where

X is Linear ma Value

**Example:**

### Convert 12 ma linear to square root ma

Square root mA = { √ [(X-4)/16 ] } .16 + 4

Square root mA = √((12-4)/16 ).16)+4

Square root mA = 15.31 ma

#### Articles You May Like :

DP Transmitter Error Calculations

Facts About Orifice Flow Meters

Instrument Calibration Questions

You solved my problem. Finally got the answer to my question, Linear ma to Square root ma conversion.

Dear Sir

(First of all I am sorry if I am wrong)

with due respect I would like to draw your attention on the formula

” Formula for Linear ma to Square Root ma Conversion”

what you have written is

Square root ma = square root of ((X-4)/16) x 16)+4

from my point of view it should be square root of ((X-4) x 16)+4

once again I am sorry if I am wrong …. but please correct me.

Hello Ashraf, Linear 8mA = Square root 12 mA, Just Calculate the equivalent square root mA for the linear 8mA using the above two formulas and crosscheck the results. Also Click Here for Linear to Square root Conversion Chart.

Hello Sir,

for Linear 8 ma, If I use the first formula mentioned above

Square Root ma = square root of ((X-4)/16) x 16)+4

=Square root of ((8-4)/16)x 16)+4

=Square root of ((4/16)x 16)+4

=Square root of ((1/4)x 16)+4

=Square root of 4 + 4

=2 + 4

=6

For Linear 8 ma, if I use the second formula

Square root ma = Square root of ((X-4)x 16) +4

=Square root of ((8-4)x 16)+4

=Square root of ((4)x 16)+4

=Square root of (64) +4

=8+4

=12

For your kind information, I already checked the second formula with all the Linear Value from 4 – 20 ma.

In the first formula if i am doing anything wrong, Please let me know.

Thank you so much for your prompt response.

Hello Ashraf,

for Linear 8 ma, If I use the first formula mentioned above

Square Root ma = [[square root of ((X-4)/16)] x 16]+4

= [[Square root of ((8-4)/16)] x 16]+4

=[[Square root of (0.25)] x 16]+4

= [ 0.5 x 16 ] + 4

= 8 + 4

= 12

Seems brackets are needed, so little bit confusing. Thanks.

Also you can use online tools. click here

Please explain counting for leaner 12 ma

Hello Sir,

After putting the bracket, there is no confusion.

Thank you very much.